Please help to prove this inequality.

Prove $\frac{1}{x}+\frac{1}{y}+\frac{1}{z}\geq 1$ when $(x^2-1)(y^2-1)(z^2-1)=8^3$ and each of $x,y,z$ is greater than 1.


  • $\begingroup$ This will likely require similar machinery as this other question. You are asking about the inequality on the other side, after a simple change of variables. You have the 'near equality' case of $x \rightarrow 1, y, z \rightarrow \infty$ to take care of. $\endgroup$ – Calvin Lin Jul 19 '13 at 16:26
  • $\begingroup$ Not necessarily. The minimum is reached when the $x,y,z$ are equal here. $\endgroup$ – user85356 Jul 19 '13 at 16:33

Write the means $$ \begin{align} H &= \frac{3}{\frac{1}{x}+\frac{1}{y}+\frac{1}{z}} \\ G &= \sqrt[3]{xyz} \\ A &=\left(\frac{x+y+z}{3}\right) \end{align} $$ then the power mean (AM-GM-HM) inequality gives $H \le G \le A$. Also note $$ xy+yz+zx = xyz\left(\frac{1}{x}+\frac{1}{y}+\frac{1}{z}\right)=\frac{3G^3}{H} $$

Now given $$ \begin{align} 8^3 &= (x^2-1)(y^2-1)(z^2-1) \\ &= (x-1)(y-1)(z-1)(x+1)(y+1)(z+1) \\ &= (xyz-(xy+yz+zx)+(x+y+z)-1)(xyz+(xy+yz+zx)+(x+y+z)+1) \\ &= \left(G^3\left(1-\frac{3}{H}\right)+3A-1\right) \left(G^3\left(1+\frac{3}{H}\right)+3A+1\right) \end{align} $$ Then we have either $$ 1-\frac{3}{H} < 0 \\ \implies H < 3 \implies 1< \frac{1}{x}+\frac{1}{y}+\frac{1}{z} $$ or else $$ 1-\frac{3}{H} \ge 0 \\ \implies G^3(1-3/H) \ge H^3(1-3/H) = H^3-3H^2 $$ and hence $$ \begin{align} 8^3 &= \left(G^3\left(1-\frac{3}{H}\right)+3A-1\right) \left(G^3\left(1+\frac{3}{H}\right)+3A+1\right) \\ &\ge (H^3-3H^2+3H-1)(H^3+3H^2+3H+1) \\ &= (H-1)^3(H+1)^3 \\ &= (H^2-1)^3 \\ \implies H &\le 3 \\ \implies 1 &\le \frac{1}{x}+\frac{1}{y}+\frac{1}{z} \end{align} $$

  • $\begingroup$ One typo: the quadratic mean is a square root, nota square. Although this doesn't affect your results, it is worth noting. Also am gm would work well intead of Cauchy-shwarz $\endgroup$ – chubakueno Jul 20 '13 at 5:07
  • $\begingroup$ Another typo on the final lines: $H \le 3$, Again, this doesnt affect your results $\endgroup$ – chubakueno Jul 20 '13 at 5:15
  • $\begingroup$ One last thing that may be critical and went unnoticed: when you change the sign of the inequality you have, you also change it's direction. That does affect and I couldn't find a fast-repair...If I come up with a solution, i will post it here. Meanwhile, that negative sign is doing our lives impossible. $\endgroup$ – chubakueno Jul 20 '13 at 5:50
  • $\begingroup$ I agree. The inequality involving $-3G^6/H^2$ in the middle does not hold. $\endgroup$ – user85356 Jul 20 '13 at 14:38
  • $\begingroup$ Substantially rewritten. Is there still a problem? $\endgroup$ – Zander Jul 22 '13 at 11:55

Let $x^2-1=\frac{8bc}{a^2}$, $y^2-1=\frac{8ac}{b^2}$ and $z^2-1=\frac{8ab}{c^2}$, where $a$, $b$ and $c$ are positives.

Hence, by Holder we obtain: $$\sum_{cyc}\frac{1}{x}=\sum_{cyc}\frac{1}{\sqrt{1+\frac{8bc}{a^2}}}=\sum_{cyc}\frac{a}{\sqrt{a^2+8bc}}=$$ $$=\sqrt{\frac{\left(\sum\limits_{cyc}\frac{a}{\sqrt{a^2+8bc}}\right)^2\sum\limits_{cyc}a(a^2+8bc)}{\sum\limits_{cyc}a(a^2+8bc)}}\geq\sqrt{\frac{(a+b+c)^3}{\sum\limits_{cyc}a(a^2+8bc)}}=$$ $$=\sqrt{\frac{\sum\limits_{cyc}(a^3+3a^2b+3a^2c+2abc)}{\sum\limits_{cyc}(a^3+8abc)}}=\sqrt{\frac{\sum\limits_{cyc}(a^3+8abc)+3\sum\limits_{cyc}c(a-b)^2}{\sum\limits_{cyc}(a^3+8abc)}}\geq1.$$ Done!


By symmetry, the minimum value of the expression


under the constraint $(x^2-1)(y^2-1)(z^2-1)=8^3$ will occur when $x=y=z$. From this, it follows that the minimum occurs when $x=y=z=3$, and the minimum is $1$.

  • 1
    $\begingroup$ And by symmetry the minimum of $x^2+y^2+z^2$ when $x^4+y^4+z^4=1$ occurs when... $\endgroup$ – N. S. Jul 19 '13 at 16:19
  • $\begingroup$ Simmetry is a good point to start, but it is not a complete proof. $\endgroup$ – chubakueno Jul 19 '13 at 16:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.